Hospitality Students’ Perception of College Library Service Quality: Importance- Performance Analysis - Mallya, Jyothi; Patwardhan, Vidya (DESIDOC Journal of Library & Information Technology, 2018)
The purpose of this research is to examine the perceived importance and perceived experiences of library service quality for hospitality management students. Also, an effort was made to identify the strengths and weaknesses of library service quality based on their perception of library services. The researchers have used LibQUAL+®, a popular tool that libraries use to assess the perception of library service quality over the years. Undergraduates and postgraduate’s students studying in one of the premier private hotel management institutes in India participated in this study. The findings of the study suggest that library service providers need to understand the needs of students and should have the inclination to help students in making the library a gateway for study, learning and research. The future research may include faculty members’ perception of importance and performance of library service quality. This type of survey can be repeated at regular intervals to distinguish the varying needs of library users.